PEMANFAATAN TUMBUHAN OBAT OLEH MASYARAKAT DI DESA WATATU KECAMATAN BANAWA SELATAN KABUPATEN DONGGALA SULAWESI TENGAH - Fhandika, Bayu; Wahid, Abdul (Jurnal Warta Rimba, 2020)
Indonesia was tropical nation which had known as producer of various communities, including among of them were medical herbs. The variety numbers of medical herbs which had in Wattatu Village could not be identified until now, so the medical herbs needed to be documented as raw materials. The purpose of this research was to identify the benefit of medical herbs. This research was conducted through descriptive qualitative method in Watatu Village. The determination of sample used purposive sampling which amount 26 informants which consisted of 1 key informant, 5 hamlets people, 5 hamlets people II, 5 hamlets people III, 5 hamlets people IV and 5 hamlets people. The technique of data collection was observation, interview, and documentation. The data analyzing conducted through three steps, they were data reduction, presentation, and collecting of conclusion. The result of this research showed that society of Watatu Village still used medical herbs. There were some kinds of medical herbs which were used by society to treat several of disease. The parts of medical herbs which used as medical were fruits, rhizomes, bulbs, leafs, seed, stems, roots, flowers and sap. The society understanding of medical herbs was through hereditary knowledge, shaman, friends and internet. The medical herbs obtained from house yard, garden, forest, and growing wild medicine. During the society taken the advantage of medical herbs, they always felt that there was changing of their disease.Keywords : Medical, Herbs, Hamlets